Accuracy of Revised Tokuhashi Scoring System and Prognostic Factors to Predict Life Expectancy in Lung Cancer Patients with Spinal Metastasis - Choovongkomol, MD, Kongtush; Sirisopikun, MD, Veerapat; Piyapromdee, MD, Urawit; Tanaviriyachai, MD, Terdpong; Jongkittanakul, MD, Sarut (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: This study aimed to verify the accuracy of the revised Tokuhashi scoring system to identify the prognosis and life expectancy of lung cancer patients with spinal metastasis. We also aimed to find the factors that were related to the prognosis and actual death. Method: Lung cancer patients with spinal metastasis who were diagnosed between January 2014 to December 2018 were included in this study. Demographic data, radiographic data, revised Tokuhashi score parameters, actual death, and treatment administered were collected from the hospital tumor database. The relationship between each parameter and actual death were collected and multivariable logistic regression analysis was used to explore the associated factors. Results: Totally 181 patients were included in this study. The accuracy of the revised Tokuhashi scoring system in this study was 80.68% for scores 0-8 and 100% for scores ≥ 9. Sensitivity and specificity were 100%and 80.7%, respectively, for the prediction of life expectancy ≥ 6 months. LR+ was 5.18. Female (HR=0.58, P=0.001), good general condition (HR=0.34, P=0.036), none of extra spinal foci metastasis (HR=0.40, P=0.002), 1 or 2 extra spinal foci metastasis (HR=0.54, P=0.003), radiation (HR=0.57, P=0.02), and chemotherapy (HR=0.51, P=0.004) were the associated factors with statistical significance. Conclusion: The revised Tokuhashi scoring system for lung cancer with spinal metastasis had satisfactory accuracy rate to predict life expectancy, especially for > 6 months (score ≥ 9). We also found that females, good general condition, number of extra spinal foci < 3, radiation, and chemotherapy were significantly good prognoses for life expectancy.